The Blockade of TACE-Dependent EGF Receptor Activation by Losartan-Erlotinib Combination Attenuates Renal Fibrosis Formation in 5/6-Nephrectomized Rats Under Vitamin D Deficiency - Gonçalves, Janaína Garcia; Canale, Daniele; de Bragança, Ana Carolina; Seguro, Antonio Carlos; Shimizu, Maria Heloisa Massola; Volpini, Rildo Aparecido (Frontiers in Medicine, 2021)
Chronic kidney disease (CKD) has been considered a major public health issue. In addition to cardiovascular diseases and infections, hypovitaminosis D has been considered a non-traditional aggravating factor for CKD progression. Interstitial fibrosis is a hallmark of CKD strongly correlated with deterioration of renal function. Transforming growth factor β (TGF-β) is the major regulatory profibrotic cytokine in CKD. Many injurious stimuli converge on the TGF-β pathway, which has context-dependent pleiotropic effects and interacts with several related renal fibrosis formation (RFF) pathways. Epidermal growth factor receptor (EGFR) is critically involved in CKD progression, exerting a pathogenic role in RFF associated with TGF-β-related fibrogenesis. Among others, EGFR pathway can be activated by a disintegrin and a metalloproteinase known as tumor necrosis factor α-converting enzyme (TACE). Currently no effective therapy is available to completely arrest RFF and slow the progression of CKD. Therefore, we investigated the effects of a double treatment with losartan potassium (L), an AT1R antagonist, and the tyrosine kinase inhibitor erlotinib (E) on the alternative pathway of RFF related to TACE-dependent EGFR activation in 5/6-nephrectomized rats under vitamin D deficiency (D). During the 90-day protocol, male Wistar rats under D, were submitted to 5/6 nephrectomy (N) on day 30 and randomized into four groups: N+D, no treatment; N+D+L, received losartan (50 mg/kg/day); N+D+E, received erlotinib (6 mg/kg/day); N+D+L+E received losartan+erlotinib treatment. N+D+L+E data demonstrated that the double treatment with losartan+erlotinib not only blocked the TACE-dependent EGF receptor activation but also prevented the expression of TGF-β, protecting against RFF. This renoprotection by losartan+erlotinib was corroborated by a lower expression of ECM proteins and markers of phenotypic alteration as well as a lesser inflammatory cell infiltrate. Although erlotinib alone has been emerging as a renoprotective drug, its association with losartan should be considered as a potential therapeutic strategy on the modulation of RFF.